Monte Carlo calculations in nuclear medicine : therapeutic applications - Zaidi, Habib (IOP (Series). Release 22., 2022)
This book covers the applications of Monte Carlo (MC) calculations in therapeutic nuclear medicine from basic principles, to computer implementations of software packages and their applications in radiation dosimetry and treatment planning in targeted radionuclide therapy.